Development of Wetland Ethnoscience E-Magazine Based on Scientific Critical Thinking Model to Improve Students' Critical Thinking Skills and Scientific Literacy - Rusmansyah; Abdul Hamid; Mohamad Nor Aufa; Isnawati; Arief Ertha Kusuma (Jurnal Penelitian Pendidikan IPA, 2023)
This research is based on students' low critical thinking skills and scientific literacy in their ability to absorb the subject matter. So to overcome these problems, and based on an initial needs analysis, an innovative learning resource was created in the form of an e-magazine which aims to facilitate the student learning process and improve students' critical thinking and science literacy skills. This research is a Research and Development (R & D) type of research to describe the validity of the Wetland Ethnoscience E-Magazine Based on the Scientific Critical Thinking (SCT) Model to be able to improve students' skills in terms of critical thinking skills and scientific literacy. The development model used is ADDIE, which consists of five stages: analysis, design, development, implementation, and evaluation. The results of research into the feasibility test of the product quality of E-Magazine Ethnoscience Wetlands Based on the SCT Model, which experts have validated, obtained an average validation score of 4.57, which is in the very valid criteria range. Based on this, the e-magazine is suitable and can be used in teaching and learning activities, especially in improving students' critical thinking skills and scientific literacy in chemistry learning.